Invasive legumes can associate with many mutualists of native legumes, but usually do not. Issue 20 (17th September 2017) - La Pierre, Kimberly J.; Simms, Ellen L.; Tariq, Mohsin; Zafar, Marriam; Porter, Stephanie S.
Abstract: Mutualistic interactions can strongly influence species invasions, as the inability to form successful mutualisms in an exotic range could hamper a host's invasion success. This barrier to invasion may be overcome if an invader either forms novel mutualistic associations or finds and associates with familiar mutualists in the exotic range. Here, we ask (1) does the community of rhizobial mutualists associated with invasive legumes in their exotic range overlap with that of local native legumes and (2) can any differences be explained by fundamental incompatibilities with particular rhizobial genotypes? To address these questions, we first characterized the rhizobial communities naturally associating with three invasive and six native legumes growing in the San Francisco Bay Area. We then conducted a greenhouse experiment to test whether the invasive legume could nodulate with any of a broad array of rhizobia found in their exotic range. There was little overlap between the Bradyrhizobium communities associated with wild‐grown invasive and native legumes, yet the invasive legumes could nodulate with a broad range of rhizobial strains under greenhouse conditions. These observations suggest that under field conditions in their exotic range, these invasive legumes are not currently associating with the mutualists of local native legumes, despite their potential to form such associations. However, the promiscuity with which these invading legumes can form mutualistic associations could be an important factor early in the invasion process if mutualist scarcity limits range expansion. Overall, the observation that invasive legumes have a community of rhizobia distinct from that of native legumes, despite their ability to associate with many rhizobial strains, challenges existing assumptions about how invading species obtain their mutualists. These results can therefore inform current and future efforts to prevent and remove invasive species. Abstract : Mutualistic interactions may be important drivers of species invasions. Here, we ask whether the community of rhizobial mutualists associated with invasive legumes in their exotic range overlaps with that of local native legumes. We found that invasive legumes utilize a distinct set of rhizobia from native legumes, despite an ability to broadly associate with many rhizobial strains, challenging existing assumptions about how invading species obtain their mutualists.